New records of shore flies (Diptera, Ephydridae) from Morocco - Rachida Akhrif; Khalid Aattouch; Mourad Beni-Eich; Paul L.Th. Beuk; Khadija Bouzrarf; Abdellatif Akarid; Boutaïna Belqat (Journal of Insect Biodiversity and Systematics)
Among the 45 collected and identified species, one genus (Scoliocephalus Becker, 1903) and nine species of shore flies (Diptera, Ephydridae) are recorded for the first time in Morocco of which seven species are new to the North African region (Gymnoclasiopa aulisioi (Canzoneri, 1976), Gymnoclasiopa flavoantennata (Strobl, 1900), Hydrellia fascitibia (von Roser, 1840), Philotelma rossii (Canzoneri & Meneghini, 1979), Scatophila mesogramma (Loew, 1862), Scatophila quadriguttata (Meigen, 1830) and Scatophila signata (Loew, 1860)). New data on the distribution of 23 other species are provided: twenty, six and two species are, respectively new for the Rif, the High Atlas, and the Middle Atlas Mountains, whereas one species is new for each of the Central Plateau and the Anti Atlas Mountains. These findings increased the number of Ephydridae species recorded in Morocco to 126 species in 44 genera. They contribute significantly to the understanding of the biodiversity and biogeographical distribution of the Ephydridae family in Morocco and North Africa. The Ephydrids fauna of Morocco account for 6.1% of the world’s known species.